THE EFFECTIVENESS OF MAKING VIDEO BLOG (VLOG) TO MINIMIZE STUDENTS’ ANXIETY IN PUBLIC SPEAKING ON DESCRIPTIVE TEXT MATERIAL - Dani Fitria Brilianti; Arief Zul Fauzi (Universitas Putera Batam, 2020)
The ability in to speak English in the public place being a scourge for students due to minimize the anxiety because of lack of speaking practice in their life, so that an effective media is needed to decrease the students’ anxiety in speaking by making video blog (VLOG) . The aims of this study are to minimize students’ anxiety in public speaking that focus on descriptive text teaching materials, and to improve students’ speaking skills in the context of description through VLOG media. The subjects in this study is the student of DIII Computer Engineering at the Polytechnic of Harapan Bersama Tegal with a qualitative descriptive research approach by using the Classroom Action Research (CAR) method in two cycles, each of the cycle consists of four stages of planning, implementation, observation, and reflection. The data collection method in this study is to use a questionnaire, interview, observation, and reflection in accordance with the Action Research guidelines. The finding showed that the average of pre test score was only 52.5, after treating by video blog it was improved to 74.5 in cycle 1, then it improved more in cycle 2 and reached 87.3. So, it improved 34.8 point from pre test to the post test. In line with the data, designing video blog is effective to minimize students’ anxiety in teaching spoken descriptive test and it works to improve the students speaking skill. Moreover, students also get their own motivation to speak confidently in the public place. Some aspects that improved are fluency, pronunciation, vocabulary items and content. As the final result, it can be inferred that making video blog minimize students’ anxiety in speaking and it improves students’ speaking performance.